Ecrire et souffrir : L’inspiration partagée de Constance Fenimore Woolson et de Henry James - Jeannine Hayat (Revue LISA)
Miss Grief is a story by Constance Fenimore Woolson, an American novelist who often wrote about the difficulty a woman had in becoming an artist — a writer or a painter — in the nineteenth century. This tale is a very strange text, a kind of anticipation of a meeting to come, in Italy, in 1880, between Woolson and Henry James, and a friendship which lasted until the former’s death in 1894. For thirteen years, both writers would share a common inspiration. Death itself could not break the links between the two authors, who were connected even when settled in different European countries. William James, who was a member of the American Society for Psychical Research, probably helped his brother Henry to communicate — or so it appears — in some way with Woolson, even after her fatal accident, or possible suicide, in Venice. Henry James probably had in mind Miss Grief, a story by his dead friend, before writing some of his books. Indeed, Woolson had been the first to develop the image of “the figure in the carpet,” which was later transformed by Henry James. Woolson was also the first to devise a plot which Henry James would later use as a canvas for his novel The Wings of the Dove. What is an author and what is authorship? It seems impossible to separate what is Woolson’s and what is Henry James’s in four works of fiction that are in fact to be read together : Miss Grief, The Figure in the Carpet, The Beast in the Jungle, The Wings of the Dove.